Why Always Women?: Gender Inequality in Rusmini’s “Kenanga” (A Feminist Criticism Study) - Apriani Riyanti; Umul Khasanah; Indriyati Kamil; Ni Putu Juliani Lestari Dewi; Imelda S. Lolowang (English Education Department, 2023)
The issue of gender equality is no longer a new one. It arises along with the stereotype of men who have a higher nature than women. In addition, in terms of strength and rights women are also below men. This aspect of gender inequality is one of the aspects developed by Rusmini in her novel